Functional genomic analysis identifies drug targetable pathways in invasive and metastatic cutaneous squamous cell carcinoma - Anderson, Ashley N; McClanahan, Danielle; Jacobs, James; Jeng, Sophia; Vigoda, Myles; Blucher, Aurora S; Zheng, Christina; Yoo, Yeon Jung; Hale, Carolyn; Ouyang, Xiaoming; Clayburgh, Daniel; Andersen, Peter; et al. (Cold Spring Harbor molecular case studies, 2020)
Although cutaneous squamous cell carcinoma (cSCC) is treatable in the majority of cases, deadly invasive and metastatic cases do occur. To date there are neither reliable predictive biomarkers of disease progression nor FDA-approved targeted therapies as standard of care. To address these issues, we screened patient-derived primary cultured cells from invasive/metastatic cSCC with 107 small-molecule inhibitors. In-house bioinformatics tools were used to cross-analyze drug responses and DNA mutations in tumors detected by whole-exome sequencing (WES). Aberrations in molecular pathways with evidence of potential drug targets were identified, including the Eph-ephrin and neutrophil degranulation signaling pathways. Using a screening panel of siRNAs, we identified EPHA6 and EPHA7 as targets within the Eph-ephrin pathway responsible for mitigating decreased cell viability. These studies form a plausible foundation for detecting biomarkers of high-risk progressive disease applicable in dermatopathology and for patient-specific therapeutic options for invasive/metastatic cSCC.